Elaboration of the collective catalogue of periodical publications of the documentary information units of the Faculty of Social Sciences of the National University. - González Carvajal, Errol (2009)
The results of the final graduation practice called "Creation of the Collective Catalogue of Periodic Publications of the Documentary Information Units of the Faculty of Social Sciences of the National University" are presented, which consisted of the creation of an automated catalogue for periodical publications through the GENISIS program. Of the documentary information units: of the Faculty of Social Sciences of the National University: CIDCSO (Social Sciences Documentary Information Center), FBEH (Bibliographic Fund of the School of History), RI (Specialized Library in International Relations "Luis y Felipe Molina") and CINPE (Library of the National Center for Economic Policy in Sustainable Development).